DNA-based client puzzle for wlan association protocol against connection request flooding - Ali Ordi, 1979- author 605584; Mazdak Zamani, 1979-, supervisor 501962; Norbik Bashah Idris, supervisor 317385; Sekolah Informatik Termaju 599676 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Thesis (Doktor Falsafah)